Submissão e resistência: representações femininas n’As luzes de Leonor, de Maria Teresa Horta - Lima, Jaqueline Vieira de (2022)
This Dissertation presents a study about the contemporary historical novel As Luzes de Leonor, a Marquesa de Alorna, uma sedutora de anjos, poetas e heróis (2012) by the portuguese author Maria Tereza Horta. Our aim is to do a critical analysis of this narrative searching to identify how the historical figures Leonor of Almeida, Leonor of Távora, Leonor of Lorena and Maria Rita are represented. From the perspective of the Gender Studies, we have observed how they behaviour themselves in front of the male opression that they were submitted. Taking into consideration the fact that it treats about a built representation by the female authorship into contemporary historical fiction thus we also have done the utilization of the studies of the Feminist Literary Criticism and the Contemporary Historical Novel. We have started from the hypotesis that even these characters are inserted into a opresssive and machist sociocultural context and with their all lives marked by the atrocities made by the political power and by the male domination, they behaviour themselves in different ways; meawhile, two of them accepted the imposed destine, the other ones, drawing upon possible tricks, they resisted and did not resigned themselves. In this way, between the several profiles of women who lived in the portuguese society of the XVIII century, our analysis shows two kinds which are important in this work: the one of the women who followed the standards, keeping themselves as submissed; and the ones who did not submitted to the currrent values but were equal precluded by the official historiography. This research has a bibliographical slant whose approach used was the indutive and interpretative methods. For the theoretical basis of our research, we have relied on, amongst others, the studies by Elaine Showalter (1994); Toril Moi (1988); Macedo e Amaral (2005); Maria de Fátima Marinho (1999); Cristina Vieira (2002); Linda Hutcheon (1991); Michelle Perrot (2017, 2005); Michèle Crampe Casnabet (1991); Arilda Ribeiro (2002); Maria Antônia Lopes (1989, 2017, 2019); Vanda Anastácio (2007a, 2007b, 2009); Pierre Bourdieu (2012); Simone de Beauvoir (2016); Elisabeth Badinter (1985); At the end of this study, we have founded that all the four characters had the consciouness of the opression who lived, however, Leonor of Lorena e Maria Rita did not find strengths to react and try to change the course of their lives; thus, they silent their true desires and suffer with an unhappy married life. Already Leonor of Távora and Leonor of Almeida never stopped fighting for what they believed in, either by explicitly challenging the dominant powers or using pretense as a mechanism of resistance.